Black Hole-Inspired Optimal Design of Biomethane Liquefaction Process for Small-Scale Applications - He, Tianbiao; Qyyum, Muhammad Abdul; Zhou, Zhongming; Ahmad, Ashfaq; Rehan, Mohammad; Nizami, Abdul-Sattar; Lee, Moonyong (Frontiers in Energy Research, 2021)
Biomethane is regarded as a promising renewable energy source, with great potential to satisfy the growth of energy demands and to reduce greenhouse gas emissions. Liquefaction is a suitable approach for long distances and overseas transportation of biomethane, however, it is energy-intensive due to its cryogenic working condition. The major challenge is to design a high-energy efficiency liquefaction process with simple operation and configuration. A single mixed refrigerant biomethane liquefaction process adopting the cryogenic liquid turbine for small-scale production has been proposed in this study to address this issue. The optimal design corresponding to minimal energy consumption was obtained through the black-hole-based optimization algorithm. The effect of the minimum internal temperature approach (MITA) in the main cryogenic heat exchanger on the biomethane liquefaction process performance was investigated. The study results indicated that the specific energy consumption of the modified case 2 with MITA of 2 °C was 0.3228 kWh/kg with a 21.01% reduction compared to the published base case. When the MITA decreased to 1 °C, the specific power of the modified case 1 reduced to 0.3162 kWh/kg, which was 24.96% lower than the base case. In terms of exergy analysis, the total exergy destruction of the modified cases 1, 2, and 3 was 31.28%, 22.27%, and 17.51% lower than the base case. This study's findings suggested that introducing a cryogenic liquid turbine to the single mixed refrigerant-based biomethane liquefaction process could reduce the specific energy consumption and total exergy destruction significantly. Therefore, this study could provide a viable path for designing and improving the small-scale biomethane liquefaction process.